The future of Global Environmental Assessments: 20 years after the Millennium Ecosystem Assessment - Elena Michele Bennett; Walter Reid; Stephen Carpenter; Tom Dietz; Garry Peterson; Neville Ash; T Doug Beard; Silke Beck; Reinette Biggs; Noel Castree; John Ehrmann; Tim Forsyth; et al. (Current Opinion in Environmental Sustainability, 2026)

Mid-crustal strain localisation triggered by localised fluid influx and activation of dissolution–precipitation creep - Manon Carpenter; Sandra Piazolo; Tim Craig; Tim J. Wright (Journal of Structural Geology, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Surface Inorganic Iodine Speciation in the Indian and Southern Oceans From 12°N to 70°S - Rosie Chance; Liselotte Tinel; Amit Sarkar; Alok K. Sinha; Anoop S. Mahajan; Racheal Chacko; P. Sabu; Rajdeep Roy; Tim D. Jickells; David P. Stevens; Martin Wadley; Lucy J. Carpenter (Frontiers in Marine Science, 2020)

In Response to Borgsteede et al. About Bupropion and Serotonin Toxicity - Brian Patrick Murray; Joseph Carpenter; Tim P. Moran; Diane P. Calello; Ziad Kazzi (Journal of Medical Toxicology, 2020)

Single-Agent Bupropion Exposures: Clinical Characteristics and an Atypical Cause of Serotonin Toxicity - Brian Murray; Joseph Carpenter; Camille Dunkley; Tim P. Moran; Emily A. Kiernan; Tony Rianprakaisang; Waleed S. Alsukaiti; Diane P. Calello; Ziad Kazzi (Journal of Medical Toxicology, 2020)

Naloxone Dosing After Opioid Overdose in the Era of Illicitly Manufactured Fentanyl - Joseph Carpenter; Brian Patrick Murray; Sukhshant Atti; Tim P. Moran; Arthur Yancey; Brent Morgan (Journal of Medical Toxicology, 2020)

Does Lidocaine Cause False Positive Results on Cocaine Urine Drug Screen? - Eungjae Kim; Brian Patrick Murray; Maryam Salehi; Tim P. Moran; Joseph E. Carpenter; David D. Koch; James C. Ritchie; Joanna M. Schindler; Brent W. Morgan (Journal of Medical Toxicology, 2019)

Life table invasion models: spatial progression and species‐specific partitioning - Zihua Zhao; Cang Hui; Richard E. Plant; Min Su; Tim Carpenter; Nikos Papadopoulos; Zhihong Li; James R. Carey (Ecology, 2019)
Biological invasions are increasingly being considered important spatial processes that drive global changes, threatening biodiversity, regional economies, and ecosystem functions. A unifying conceptual model of the invasion dynamics could serve as a useful tool for comparison and classification of invasion processes involving different species across large geographic ranges. By dividing these geographic ranges that are subject to invasions into discrete spatial units, we here conceptualize the invasion process as the transition from pristine to invaded spatial units. We use California cities as the spatial units and a long‐term database of invasive tropical tephritids to characterize the invasion patterns. A new life‐table method based on insect demography, including the progression model of invasion stage transition and the species‐specific partitioning model of multispecies invasions, was developed to analyze the invasion patterns. The progression model allows us to estimate the probability and rate of transition for individual cities from pristine to infested stages and subsequently differentiate the first year of detection from detection recurrences. Importantly, we show that the interval of invasive tephritid recurrence in a city declines with increasing invasion stages of the city. The species‐specific partitioning model revealed profound differences in invasion outcome depending on which tephritid species was first detected (and then locally eradicated) in the early stage of invasion. Taken together, we discuss how these two life‐table invasion models can cast new light on existing invasion concepts; in particular, on formulating invasion dynamics as the state transition of cities and partitioning species‐specific roles during multispecies invasions. These models provide a new set of tools for predicting the spatiotemporal progression of invasion and providing early warnings of recurrent invasions for efficient management.

Decrease in Sightings of Sixgill Sharks, Hexanchus griseus, in Elliott Bay, Seattle, WA, United States, a Comparison Between 2003–2005 and 2008–2015 - Denise Griffing; Jeff Christiansen; Joel Hollander; Tim Carpenter; Shawn Larson (Frontiers in Marine Science, 2019)

The application of GIS and spatiotemporal analyses to investigations of unusual marine mammal strandings and mortality events - Stephanie A. Norman; Jessie Huggins; Tim E. Carpenter; James T. Case; Dyanna M. Lambourn; Jim Rice; John Calambokidis; Joseph K. Gaydos; M. Bradley Hanson; Deborah A. Duffield; Sandra Dubpernell; Susan Berta; et al. (Marine Mammal Science, 2012)
In 2006–2007, an unusually high number of harbor porpoises ( Phocoena phocoena ) stranded along the Washington and Oregon coastlines. Spatiotemporal analyses were used to examine their ability to detect clusters of porpoise strandings during an unusual mortality event (UME) in the Pacific Northwest using stranding location data. Strandings were evaluated as two separate populations, outer coast and inland waters. The presence of global clustering was evaluated using the Knox spatiotemporal test, and the presence of local clusters was investigated using a spatiotemporal scan statistic (space–time permutation). There was evidence of global clustering, but no local clustering, supporting the hypothesis that strandings were due to more varied etiologies instead of localized causes. Further analyses at subregional levels, and concurrently assessing environmental factors, might reveal additional geographic distribution patterns. This article describes the spatial analytical tools applied in this study and how they can help elucidate the spatiotemporal epidemiology of other UMEs and assist in determining their causes. More than one spatial analytical technique should be used if the study objective is to detect and describe clustering in time and space and to generate hypotheses regarding causation of marine mammal disease and stranding events.

Temporal-spatial epidemiology of foot-and-mouth disease outbreaks in Mongolia, 2000 – 2002 - Enkhtuvshin Shiilegdamba; Tim E. Carpenter; Andrés M. Perez; Mark C. Thurmond (Veterinary Research Communications, 2008)